2017
DOI: 10.25221/fee.345.2
|View full text |Cite
|
Sign up to set email alerts
|

New records of lithobiid centipedes (Chilopoda: Lithobiomorpha) from Western Mongolia

Abstract: Summary. New data on distribution of three lithobiid species in Western Mongolia are given. Lithobius sibiricus Gerstfeldt, 1858 is recorded from this territory for the first time and L. giganteus Sseliwanoff, 1881 is new for Khovd Aimag. Data on distribution and habitats of a poorly known Schizotergitius altajicus Loksa, 1978 are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The study of the material from western Mongolia (Dyachkov 2017(Dyachkov , 2018Farzalieva et al 2017) also revealed specimens of Polyporogaster porosa (Sseliwanoff, 1881). To date, himantariids have never been reported from this region.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The study of the material from western Mongolia (Dyachkov 2017(Dyachkov , 2018Farzalieva et al 2017) also revealed specimens of Polyporogaster porosa (Sseliwanoff, 1881). To date, himantariids have never been reported from this region.…”
Section: Introductionmentioning
confidence: 98%
“…The centipede fauna of this country is still studied fragmentarily. To date, 6 families of 3 orders of Chilopoda are known from Mongolia: Scutigeridae (Scutigeromorpha), Lithobiidae and Henicopidae (Lithobiomorpha), Geophilidae, Linotaeniidae, and Schendylidae (Geophilomorpha) (Sseliwanoff 1878(Sseliwanoff , 1881c(Sseliwanoff , 1881dAttems 1901;Verhoeff 1934Verhoeff , 1942Dobroruka 1960Dobroruka , 1970Loksa 1965Loksa , 1978Zalesskaja 1978;Eason 1986;Ulykpan 1988;Poloczek et al 2016Poloczek et al , 2017Dyachkov 2017Dyachkov , 2018Farzalieva et al 2017).…”
Section: Introductionmentioning
confidence: 99%